Basilia de Jesús y Magdalena Bentura: mujeres carmelitas agentes de su propio arte en el siglo XVIII - Adriana Saenz Tapia (Bulletin de l'Institut Français d'Études Andines)
This article proposes the study of the artwork Acvérdate de tvs postrimerías, y jamás pecarás (1704), an oil canvas belonging to the private collection of the Discalced Carmelites of Ayacucho. From the information provided by the piece itself, such as the name of the commissioner Sister Basilia de Jesús or the possible artist Sister Magdalena Bentura del Santissimo Sacramento, we propose an historical and iconographic approach, as well as a gender approach. Thus, our analysis starts from the particularities that enhanced the uniqueness of the work to the analysis of the context of two women viewed as cultural agents.